Diseño del proceso de gestión de peticiones, quejas, reclamos y sugerencias de la empresa Caudales y Muestreos S.A.S. (2020)
This project aims to design the management process of PQRS in the company Caudales y Muestreos S.A.S, based on the guidelines of ISO 10002 and the structure of the PHVA cycle. Claims management is a determining element in the quality of service and customer service, it must be dynamic, flexible and adaptable to the needs of any organization, oriented to the improvement of processes and customer satisfaction. The stability of companies and their competitive character in the market lies in their ability to reinvent so that each process meets the current demands and needs of domestic trade and industry.